Konsep sabar dalam al-qur’an serta relevansinya dengan psikologi positif - Mazidatun, Dewi Aulia (Maliki Interdisciplinary Journal, 2025)
The purpose of this study is to examine the concept of patience in the Qur’an through a thematic interpretation (maudhu’i) approach and to examine its relevance to positive psychology theory. Patience is one of the main moral and spiritual values ​​in Islam that is closely related to individual psychological resilience. This study uses a qualitative library research method, with primary sources consisting of Qur’anic verses about patience, while secondary sources include interpretations, positive psychology literature, and literature supporting this research. The results of the study indicate that patience in the Qur’an does not only have a passive meaning in facing trials, but also includes an active dimension in the form of moral steadfastness, self-control, and optimism for goodness. The positive psychology perspective strengthens this understanding by positioning patience as an adaptive coping mechanism that can increase individual resilience and well-being. The integration of these two perspectives shows that the concept of patience can be a constructive foundation for Islamic ethics and psychology for the development of human character.